2020
DOI: 10.1055/s-0040-1703005
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiography Findings in Children with Febrile Convulsion

Abstract: Febrile convulsion (FC) is a seizure associated with body temperature that leads to electrocardiography changes. The study aimed to study electrocardiographic changes in children with FC as compared with healthy children. In this case–control study, 90 children aged 6 to 60 months were matched with equal healthy ones in “Ali Ebne Abi Talib” hospital in Zahedan, Iran. FC was confirmed by a neurologist based on its definition by the International League Against Epilepsy. Electrocardiogram (ECG) was captured by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…The study results disagree with that of Noori et al (15) who performed a case-control study examined the electrocardiography (ECG) results of children diagnosed with epilepsy in comparison to a control group of healthy children. Ninety patients, ages six months to eighteen, who were matched with an equivalent number of healthy youngsters made up the research sample.…”
Section: Discussioncontrasting
confidence: 99%
“…The study results disagree with that of Noori et al (15) who performed a case-control study examined the electrocardiography (ECG) results of children diagnosed with epilepsy in comparison to a control group of healthy children. Ninety patients, ages six months to eighteen, who were matched with an equivalent number of healthy youngsters made up the research sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Biet et al 18 observed a prolonged QT in epilepsy similar to a study by Kolsal et al 16 that found QTd prolonged in epilepsy compared with controls. Movahedian et al 19 and Noori et al 15 found that QT, QTc, QTd, and QTcd were higher in epilepsy patients than controls. El-Rashidy et al 20 concluded that the mean values of QTc and QTd were significantly higher in epilepsy patients.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study, we concluded that RR interval, HR, S wave in lead V 1 , R in aVL, LVM, QTd, QTc, and QTcd prolonged significantly in FC children compared with controls. 14 Kändler et al 23 found transient QTc prolongation occurred in 7 of 30 pediatric patients during a postconvulsive period of 2 hours following generalized seizures. The present study confirms that children with FC had longer QTd, QTc, and QTcd than the controls.…”
Section: Journal Of Pediatric Epilepsymentioning
confidence: 99%
See 1 more Smart Citation